Why Ukraine Matters: Putin, Power, and the Fracturing World Order - Aroshidze, Ana (European Scientific Journal, ESJ, 2025)
This article explores the geopolitical implications of Russia’s full-scale invasion of Ukraine in 2022, framing it as a pivotal event that may catalyze the formation of a new global order. The study argues that this conflict marks a reassertion of authoritarian influence against liberal democratic values and highlights the erosion of the post–Cold War international system. Using a qualitative, interdisciplinary methodology that includes discourse analysis of political speeches, journalistic sources, and strategic policy documents, the research identifies key ideological, economic, and military shifts that are reshaping global security dynamics. The literature review contextualizes the current crisis within broader historical frameworks - particularly Cold War precedents - while integrating recent findings on strategic alignment, authoritarian cooperation, and the weakening role of multilateral institutions. The analysis concludes that the United States and its allies must adopt a more adaptive and principled foreign policy in response to an increasingly multipolar and unstable world, characterized by rising geoeconomic fragmentation, nuclear escalation, and the coordinated rise of authoritarian regimes.